The integration of migrants in the German labor market: Evidence over 50 years - Paul Berbée; Jan Stuhler (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Germany has become the second-most important destination for migrants worldwide. Using all waves from the microcensus, we study their labor market integration over the last 50 years, and document key differences to the US case. While the employment gaps between immigrant and native men decline in the first years after arrival, they remain large for most cohorts; the average gap one decade after arrival is around 10 percentage points. Income gaps are instead widening with time spent in Germany. Differences in educational and demographic characteristics explain how those gaps vary across groups, and why they widened over time: accounting for composition, integration outcomes show no systematic trend. However, economic conditions do matter, and the employment rate of some earlier cohorts collapsed when structural shocks hit the German labor market in the 1990s. Finally, we study the likely integration path of recent arrivals during the European refugee 'crisis' and the Russo-Ukrainian war.
Keywords: J11; J61; J68; 330; Immigration; labor market integration; long-run trends